Orientation of Teaching, Research, and External Engagement Activities of Academics in Mexico - Haydeé Estévez-Nenniger, Etty; González-Bello, Edgar Oswaldo; Valdés-Cuervo, Angel Alberto; García-Meza, Isabel María (Acta Paedagogica Vilnensia, 2021)
Some results of the international survey Academic Profession in the Knowledge based Society (APKIS) applied in Mexico are presented. The orientation of the teaching, research, and external engagement activities, and the differentiating effect of some variables, was analyzed in a sample of 3,757 full-time academics of 116 Higher Education Institutions. Referencing the international surveys of 1992 and 2007, it was found that there are changes and continuities in the activities of Mexican academics. The type of institution variable has a generalized differentiating impact on the orientation of the activities.